Understanding procreative beneficence - Savulescu, J; Kahane, G (Oxford University Press, 2016)
Procreative beneficence (PB) prescribes that reproducers should select the child (or children) they could have, who is expected to have the best life, or at least as good a life as the others, based on the relevant, available information. Much criticized, this claim is also misunderstood: it is not an absolute obligation but similar in force to claims such as “you should give your child the best education.” This chapter clarifies the PB principle and explores competing reasons to it such as normative uncertainty, distributive justice, or reproductive liberty. It concludes that the two best objections to PB are that it requires a conception of human well-being and is committed to the existence of impersonal reasons. However, that person-affecting reasons are stronger than impersonal reasons lessens the force of some objections to PB such as that it involves sacrifices on the part of procreators.